2014
DOI: 10.1186/1471-2458-14-689
|View full text |Cite
|
Sign up to set email alerts
|

The key actors maintaining elders in functional autonomy in Bobo-Dioulasso (Burkina Faso)

Abstract: BackgroundGlobally, a significant increase in functional disability among the elderly is expected in the near future. It is therefore vital to begin considering how Sub-Saharan Africa countries can best start building or strengthening the care and support system for that target population. Study objectives are: 1) identify the key actors of the social system who maintain elders in functional autonomy at home in Bobo-Dioulasso (Burkina Faso) and 2) to describe the functional status of older people living at hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…According to Gobbens and Van Assen, this operational definition of autonomy refers not only to psychological functioning but also to physical functioning and the social environment 35. In that case, the autonomy of an older person will depend to a very large extent on both his or her physical abilities and the support capabilities of the social environment 39,40. Additional statistical analyses showed that autonomy was significantly associated with physical health (WHOQOL-BREF), physical domain (SF-12), and sensory abilities (WHOQOL-OLD), represented by Pearson’s coefficients of 0.52, 0.43, and 0.34, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gobbens and Van Assen, this operational definition of autonomy refers not only to psychological functioning but also to physical functioning and the social environment 35. In that case, the autonomy of an older person will depend to a very large extent on both his or her physical abilities and the support capabilities of the social environment 39,40. Additional statistical analyses showed that autonomy was significantly associated with physical health (WHOQOL-BREF), physical domain (SF-12), and sensory abilities (WHOQOL-OLD), represented by Pearson’s coefficients of 0.52, 0.43, and 0.34, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our interpretation of this finding is that the autonomy facet is not only psychological, but also taps into other domains such as the physical and environmental domain. Someone’s autonomy will depend to a very large extent on physical ability and the support opportunities that the environment has to offer [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is important to protect the small, elderly population in sub-Saharan Africa, and this may be easier to implement. There is limited use of institutional care for the elderly such as nursing homes, or retirement villages [19]. This may reduce the risk of nosocomial SARS-CoV-2 outbreaks in a vulnerable, captive population Since the majority of elderly people live in the rural areas, their risk of infection can be reduced by restricting movement between urban and rural areas.…”
Section: Accepted Manuscriptmentioning
confidence: 99%